The Dynamics of Foreign Bank Ownership : Evidence from Hungary - Majnoni, Giovanni (World Bank, Washington, DC, 2014)
The early start of the process of bank restructuring and privatization in Hungary provides a longer and richer amount of evidence than that available for any other transition economy. The authors analyze the dynamics of bank restructuring in Hungary with a focus on the role played by foreign ownership. They explore the performance over time of foreign-owned Hungarian banks and study the extent to which efficiency gains are affected by the chosen acquisition strategy-strategic acquisition in contrast with investment in a newly established bank (greenfield investment)-or by the management style adopted after the acquisition. The authors supplement previous results on the effects of foreign bank ownership in three ways. First, they explicitly consider the time span required for the change of ownership to affect bank performance. Second, the authors explore how important the chosen acquisition strategy is for the success of an acquisition. And third, they study how relevant the adopted management style is to this end, as proxied by the degree of reliance on foreign management.